Editors' Introduction (Journal for the study of religion, nature and culture, 2025)
This issue concludes the nineteenth volume of the Journal for the Study of Religion, Nature and Culture. The year has been marked by change within both the socio-ecological systems and diverse worldviews considered in these pages, and within the JSRNC editorial team.